Antioxidant activity of phenolic and flavonoid fractions of Cleome gynandra and Maerua angolensis of Burkina Faso - Meda N.T.R., Bangou M.J., Bakasso S., Millogo-Rasolodimby J. and O.G. Nacoulma (Journal of Applied Pharmaceutical Science, 2013)
Cleome gynandra L. and Maerua angolensis DC (Forsk) are two species of Capparidaceae family and of which the traditional uses are directed much against the inflammatory diseases, cancer and cellular ageing. The aim of this study is to measure the anti-FRAP, anti-ABTS and anti-DPPH activities through the n-hexane (n-H), dichloromethanolic (DCM), acetonitrile (ACN), ethyl acetate (EA), methanolic (MeOH) and n-butanol (n-BuOH) fractions of each species. We thus quantified the total phenolic and total flavonoids in different fractions. The whole of the tests were evaluated with a sample concentration at 100 µg/mL. Thus, three methods i.e., FRAP, ABTS and DPPH were used to estimate the total antioxidant capacity of the plants fractions. The total phenolic and total flavonoid were also determined spectrophotometrically using Folin-Ciocalteu and AlCl3 reagents, respectively. Butanolic fractions were give the bests anti-FRAP (535.961 µmol AAEAC/g of fraction), anti-ABTS (155.868 µmol TEAC/g of fraction) and anti-DPPH (81.109 µmol QEAC/ g of fraction) activities. The best phenolic content was obtained with n-butanol fraction (133.023 mg GAE/g of fraction, for C. gynandra), followed of methanolic fraction of M. angolensis (128.043 mg GAE/g of fraction). C. gynandra was give the best flavonoids contents with DCMF (50.09 %), followed of EAF (19.464 %). The obtained results allow justifying the traditional uses of these plants in the above-mentioned diseases.
Keywords: Cleome gynandra, Maerua angolensis